Factores que determinan la transferencia de conocimientos en los estudiantes de la Carrera de Ingeniería Comercial. - Avendaño Agurto, Mayra Tatiana (2017)
The research is aimed at determining the factors that limit the transfer of knowledge to the students of the Commercial Engineering Degree as a study problem. The objective of the project is to show the influential factors in the transfer of knowledge because it has been observed that there is a greater ignorance of the subject in the students, on the topics taught by the teachers in the class hours, the learning is not significant. To learn more about this problem, a theoretical, technical support was used, together with a thorough and thorough review of bibliographical sources. The methodological approach is quantitative, in the research project was carried out the application of a survey to teachers and students, descriptive research and field methods, and bibliographic are the mechanisms used for the collection of information, with which valuable information was obtained and useful for the benefit of the career, teachers and students, in the same way when tabulating the data it was observed that the scholars have deficiencies in the knowledge transfer factors such as the relationship with the student, affective communication and active learning, being active learning with greater disadvantages from both the perspective of teachers and students, the reasons that led to this consensus is that both parties have clearly identified that the classes should be largely practical and less theoretical, the students who expressed likewise problems with the relationship that exists between teacher and student. All this information contributed with results of the limitations that exist in the race to transfer the knowledge, in the end it concludes with a report in which the affectations that each factor has in the transfer of knowledge on the part of the professors are specified, towards the teachers. Finally, precise recommendations were developed for the corresponding actions on the part of those involved with teaching in higher education of the Commercial Engineering Degree at the Technical University of Cotopaxi.